Teachers' Competencies in Developing Digital Educational Escape Rooms - Yael Hakshurian (Babes-Bolyai University, 2023)
The development of digital educational escape rooms (DEERs) by teachers presents many advantages for student learning and engagement. By developing DEERs, teachers have the opportunity to customize the learning experience and align it with specific curricular goals and with the students' needs. Teachers can select the content that is relevant to the subject matter, and ensure that the puzzles and challenges within the DEERs promote the desired learning outcomes. Furthermore, a digital platform of DEERs enables a large group of students to play simultaneously, or to access the game remotely, and by this allows adjusting diverse learning environments to students' needs. For these reasons, it is crucial to understand the necessary competencies teachers need to possess to develop a successful DEER. This paper highlights these competencies, in order to promote dedicated training programs for teachers and encourage the adoption of the DEER educational approach in teaching.